Effects of elctrolytes on the stability of wetting films: Implications on seawater flotation. (15th June 2018) - Pan, Lei; Yoon, Roe-Hoan
Graphical abstract: Highlights: Wetting films on weakly hydrophobic surfaces can be stabilized by double-layer force. Metastable wetting films on hydrophobic surfaces can be destabilized by electrolytes. Hydrophobicity and hydrophobic force can be dampened by hydrolysis products of Mg 2+ ions. Sodium silicate can be used to overcome the harmful effect of the hydrolysis products. Abstract: Surface force measurements were conducted using the force apparatus for deformable surfaces (FADS) to better understand the stability of the wetting films formed on hydrophobic surfaces in the presence of KCl and MgCl2 . The measurements were conducted using thiol-coated gold surfaces as robust model hydrophobic surfaces. The results obtained in pure water show that the wetting films of water on weakly hydrophobic surfaces are metastable due to the presence of a repulsive double-layer force in the films. At high concentrations of KCl, the wetting films become unstable due to double-layer compression, causing them to rupture. In the presence of MgCl2, both contact angles and hydrophobic forces decrease due to the adsorption of the hydrolysis products such as MgOH + ions and Mg(OH)2 precipitates on the surface. The FADS data obtained in the present work were analyzed using the Frumkin-Derjaguin isotherm to determine the roles of the short- and long-range hydrophobic forces in determining the stability of the wetting films formed on hydrophobic surfaces. The results of the present study are discussed in view of the roles of electrolytes in seawater flotation.